AROME-ESO Oncology Consensus Conference: access to cancer care innovations in countries with limited resources. Association of Radiotherapy and Oncology of the Mediterranean Area (AROME-Paris) and European School of Oncology (ESO - Milan) - Todorovic, Vladimir; Aapro, Matti; Pavlidis, Nicholas; Arsovski, Oliver; Belkacemi, Yazid; Babovic, Nada; Bidard, François Clément; Bourhafour, Mouna; Beslija, Semir; Boussen, Hamouda; Cetnikovic, Bojana; Ceric, Timur; et al. (My University, 2019)
PURPOSE: Cancer is a leading cause of mortality worldwide. Its incidence is still increasing, particularly in developing countries. Recent progresses further strengthen the differences between low/middle and high-income countries. This situation calls for joint action to reduce inequities in cancer outcomes among the patients. The Association of Radiotherapy and Oncology of the Mediterranean Area (AROME) and the European School of Oncology (ESO), have initiated joint conferences devoted to access to innovations in oncology in the Mediterranean area. The heterogeneity of the economic, political and cultural situations of the different participating countries, offers the opportunity to develop consensus conference. METHODS: Cancer prevention and treatment strategies were discussed according to existing international guidelines. The Scientific committee prepared 111 questions with an objective to prioritize the access to treatments and innovations in low/middle-income Mediterranean countries. The results from the votes of 65 oncology experts, coming from 16 countries and 33 institutions have been analysed and access priorities classified accordingly. RESULTS: Ninety six percent of the proposed general recommendations concerning national health care strategies, oncology education, and treatment organization were considered to be high priorities. Regarding access to systemic treatments, 41% of the drugs without validated predictive markers and 53% of those with validated predictive markers were considered to be 1st level priority. Only 4 biological tests were considered to be 1st level priority to access to innovation. CONCLUSIONS: AROME-ESO consensus offers to cancer specialists from developing countries a basis for discussion with health authorities and payers on the prioritization of access to innovations in cancer care.